2011
DOI: 10.1016/j.otsr.2011.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Risks relating to posterior 2-portal arthroscopic subtalar arthrodesis and articular surfaces abrasion quality achievable with these approaches: A cadaver study

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
4
0
1
Order By: Relevance
“…16,25 In the present case, it was caused by osteopenia and did not The present series was too small for statistical analysis of complications. The neurovascular structures at risk were, however, similar to those in reports of subtalar arthroscopy, 2,8,13,15,18,22,23 which suggests that the rate of complications would be very low, provided the procedure was performed strictly para-Achilles; the only lesion in the present series (a peroneal artery wound) was associated with an approach that was not strictly para-Achilles but shifted laterally.…”
Section: Discussionsupporting
confidence: 80%
“…16,25 In the present case, it was caused by osteopenia and did not The present series was too small for statistical analysis of complications. The neurovascular structures at risk were, however, similar to those in reports of subtalar arthroscopy, 2,8,13,15,18,22,23 which suggests that the rate of complications would be very low, provided the procedure was performed strictly para-Achilles; the only lesion in the present series (a peroneal artery wound) was associated with an approach that was not strictly para-Achilles but shifted laterally.…”
Section: Discussionsupporting
confidence: 80%
“…With mean 93.9% and 91.1% talar and calcaneal freshening, respectively, Lintz et al (2013) [19], in a cadaver study, confirmed that lateral arthroscopic fusion ensured optimal freshening, indispensable to good fusion quality. However, despite, complete freshening on a posterior approach, Mouilhade et al (2011) [20] found imperfect contact between the freshened surfaces in 80% of cases. These fusion conditions thus seemed not to influence the fusion ratio in the present series.…”
Section: Discussionmentioning
confidence: 98%
“…The anticipated benefits include preservation of as much blood supply as possible to the healing bones to support successful fusion, diminished risk of damage to the sural nerve during the approach, and avoidance of delayed wound healing and surgical site infection. Furthermore, the two-portal sinus tarsi approach aims to avoid the significant risk to the sural nerve associated with using a posterolateral portal [26,27,32,33]. Another key benefit of this approach is by performing decortication of all three articular facets the intraoperative mobility of the arthrodesis site is improved allowing significant deformity correction.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, procedures were performed through either a posterior (posteromedial and posterolateral portals) or lateral (anterolateral and posterolateral portals) approach. One concern relating to these approaches is proximity of the posterolateral portal to the sural nerve, with a 10% incidence of nerve injury seen in cadaveric studies [26,27]. To avoid a posterolateral portal, and to access all three facets of the subtalar joint, we use a two-portal sinus tarsi approach that has previously been described in the literature [28][29][30][31] .…”
Section: Introductionmentioning
confidence: 99%